Sistem Kendali Pitch, Roll dan Ketinggian Quadcopter dengan Isyarat Tangan menggunakan Kalman Filter - Muhammad Junifadhil Caesariano; Eko Setiawan; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
UAV (Unmanned Aerial Vehicle) is an aircraft that can be controlled remotely either by humans or programmed automatically. UAV control requires a joystick controller. However, the use of a joystick as a UAV controller requires special skills in its use. Therefore, the author created a hand position-based controller that is easier to understand by people who are not familiar with the use of joysticks. However, the sensor readings are often inaccurate, therefore the Kalman Filter is used as a solution to reduce the inaccuracy. The test results show that the use of kalman filter increases the accuracy of sensor readings by using the calculation of the Root Mean Square Error. Based on testing the suitability of control using hand gestures on the movement of the UAV, the accuracy rate of control success is 85% for pitch and roll movements and 70% control success for altitude control